PENGARUH MUTU PELAYANAN KESEHATAN BPJS TERHADAP KEPUASAN PASIEN DI PUASKESMAS SEPATAN KABUPATEN TANGERANG-BANTEN TAHUN 2019 - Siti Syamsiah; Siti Nurlelah (Universitas Nasional, 2020)
Based on data from the Social Security Organizing Agency (BPJS), the number of participants in the national health insurance program (JKN) reached 196.66 million people, equivalent to 74% of Indonesia's population estimated at 265 million, from interviews with 10 patients at Sepatan Health Center, 4 people said they were satisfied, 3 people said they were satisfied and 3 people said they were not satisfied. Want to know the effect of BPJS health service quality on patient satisfaction. This study uses a descriptive Analytical Survey research design with a cross sectional approach. The sample in this study were 141 people. The sampling technique using the Random Sampling technique. The research instrument consisted of a questionnaire about the effect of BPJS health service quality on patient satisfaction. Univariate data using descriptive statistical tests and Bivariate using chi square test. Bivariate Analysis Results of the influence of BPJS health service quality on patient satisfaction based on tangible quality p value = 0,000, OR; 10,000, reliability quality p value = 0,000, OR: 27,500, responsiveness quality p value = 0,000, OR: 16,409 Assurance quality p value = 0,000, OR: 18,500 quality empathy p value = 0,000, OR: 11,765, meaning there is an influence due to the p value value <0.05. From the results of the study of respondents who came to the polyclinic in Sepatan Health Centre, 83% said they were satisfied with the quality of BPJS service at Sepatan Health Centrein 2019. For research sites to continue to maintain the quality of services, especially in BPJS patients.